Vague languages implied through disparagement functions in comic strips - Jaufillaili,; Sujatna, Eva Tuckyta Sari; Indira, Dian; Indrayani, Lia Maulia (Penerbit Universiti Kebangsaan Malaysia, 2017)
Vague language is used by speakers for many purposes. When a speaker wants to give some criticism, refusal, or deliver messages that might be unpleasant for the hearer, vague language will be one of the appropriate ways to go about it. Humor is considered the ‘smooth’ way to deliver messages that might hurt the hearer. One of the interesting forms of media toanalyse, that consistsof humor, are comic strips. However, the study on the useof vague language in comic strips is still rare. This study discusses the analysis ofvague language using Raskin’s disparagement theory of humor (1985), Grice’s Cooperative Principle and Conversational Implicature (1975). This research proposes to find out: 1) What expressions are considered as vague language in comic strips? 2) How does vague language create the humorous effects of the jokes?; and 3) How is vague language related to the disparagement functions of the jokes? It is a qualitative research, which is descriptive, involving process, meaning, and understanding gained through words or pictures (Creswell 1994). The method used is a case-study in which the data was taken from The Born Loser comic strips. The result findings show that vague language is usually reflected at the last line of the joke. Vague language creates the humorous effect of the joke by flouting the maxims and it is related to the disparagement functions based on Raskin’s theory of humor (1985) by drawing the conversational implicature. The disparagement in comic strips serves the followingfunctions; 1) to show hostility and agression, 2) to show malice and derison and 3) to show superiority.